Language Variations on TikTok Social Media - Shofiyatul Indah Setya; Siti Tuhfatus Solihah; Yunita Suryani (2022)
Language variation is the non-uniformity in one language. This study discusses variations in Indonesian on TikTok social media.Ã‚Â TikTok is now a popular social media for allÃ‚Â ages, especiallyÃ‚Â youth. The purpose of this study is to describe language variations onÃ‚Â TikTok social media. This study was studied using a sociolinguistic approach, the theory of linguistic variation. This research is descriptive qualitative, the data analyzed is in the form of speech in which there are variations in Indonesian regional dialects. The data source in this study was obtained from the social mediaÃ‚Â TikTok. The results of this study indicate that there are language variations in terms of speakers in the form of Jakarta dialect, Betawi dialect, and Surabaya dialect; while the language variation in terms of formality uses a casual variety.Ã‚Â